A CASE REPORT ON THE EFFECTS OF CYRIAX TECHNIQUE (DEEP FRICTION MASSAGE ) APPROACH TO REDUCE PAIN ON LATERAL EPICONDYLITIS - Shukla, Neha; Awasthi, Deepanita; Zaidi, Aamena; Chandrasekhar Kumar; Dixit, Anamika (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Background – tennis elbow (lateral epicondylitis) is one of the most common problems of the arm.[1] It is a work-related or sport-related pain disorder with macroscopic and microscopic tears in the extensor carpi radialis brevis [2]. Deep tendon friction (DTF) is a specific type of connective tissue massage which is applied precisely to the soft tissue structures. Deep tendon friction massage is a combination of Mill’s manipulation and is performed immediately after the DTF.[3] The purpose of this case report is to highlight the implementation of cyriax approach in lateral epicondylitis. Objective – reduction of elbow pain and improves rotational limitations. This helps in enhancing the functional activities.